1999
DOI: 10.1590/s1516-31801999000600002
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative frozen section examination in parotid gland tumors

Abstract: We consider that frozen section examination for salivary gland tumors is not sufficient on its own for deciding on the best management. Their interpretation must be correlated with clinical and intraoperative findings, in association with the surgeon's experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 9 publications
2
32
0
1
Order By: Relevance
“…27 The accuracy and potential benefit of FS in salivary gland surgery is controversially discussed in the literature. 1,5,10,23,24,27,34 Its reported sensitivity for diagnosing malignancy ranges from 43% to 100%. Most authors have shown that FS provides sensitivity rates between 60% and 80% which is similar to FNAC, and many of them have concluded that FS examination is not sufficient on its own for deciding on the best management of salivary gland lesions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…27 The accuracy and potential benefit of FS in salivary gland surgery is controversially discussed in the literature. 1,5,10,23,24,27,34 Its reported sensitivity for diagnosing malignancy ranges from 43% to 100%. Most authors have shown that FS provides sensitivity rates between 60% and 80% which is similar to FNAC, and many of them have concluded that FS examination is not sufficient on its own for deciding on the best management of salivary gland lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors have shown that FS provides sensitivity rates between 60% and 80% which is similar to FNAC, and many of them have concluded that FS examination is not sufficient on its own for deciding on the best management of salivary gland lesions. 5,10,24,27,34 The high rate of false-negative results may also be due to the following reason. When the pathologist is not sure about the diagnosis he may be inclined to give an inconclusive or benign diagnosis because he is afraid of the consequences of a malignant diagnosis for the patient at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations